Systematic Literature Review on Talent Management Effectiveness in State-Owned Enterprises (SOES) - Afifah Inayati; M. Syamsul Ma'arif; Nimmi Zulbainarni; Herien Puspitawati (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Implementing talent management effectively in state-owned enterprises (SOEs) is crucial due to large number of Indonesia's youth working therein and the contributions of Indonesian SOEs optimizing the productive workforce for national growth. However, Indonesia's experiencing global talent indices lower ranking, due to the lack of standardized effectiveness measures, limited leadership commitments impeding execution maturity, millennial turnover intentions, and leadership development struggles as an impact of digitalization.Purpose: This review aims to develop a comprehensive diagnostic framework and capability by pinpointing the highest influence effectiveness factors in talent management framework. This systematic review investigates talent management challenges to develop an integrated architecture and roadmap for enterprises, which then can be used for talent management research especially for Indonesian state-owned enterprises.Design/methodology/approach: this research conducted with systematic literature review, enriched with Publish & Perish application to map articles with high citations, followed by content analysis to answer the research question.Findings/Results: The findings suggest further studies need for multidimensional methodology by incorporating system thinking. Other previous studies focused on determining effectiveness in comparison to purposes, while many factors should be considered in determining effectivieness on implementation level.Conclusion: Comprehensive approach will enable empirical examination of correlational linkages to inform the synthesized analytical frame, aligning policies to long-range mechanisms, and continually refining frameworks amidst uncertainty with evidence-based modifications.Originality/value (State of the art): This study provides a strong foundation in developing an integrated talent management architecture and roadmap for SOEs-specific talent management research. The key impact is in the context of developing more effective talent management with extensive framework that includes process and supporting capabilities. Keywords:  BUMN, Effectiveness, state-owned enterprises, talent management, talent management implementation